Math, asked by mani1028, 11 months ago

factorise 3x²-x-4
please give correct answer

Answers

Answered by Mysteryboy01
0

{\huge{\bold{\orange{\underline{Attitude King}}}}}

\huge\mathscr\red{♡Hello♡}

\huge\mathfrak\pink{hello~friends }<font color="green">

\huge{\mathfrak{Ello!♡}}•°⭑

\huge\mathfrak\pink{hello~Good Morning }<font color="green">

\huge{\fbox{\fbox{\orange{\mathfrak{Answer\:Given }}}}}

\huge\red{\underbrace{\overbrace{\ulcorner{\mid{\overline{\underline{From\:Above}}}}}}}

<font color=red>

3x² - x - 4

3x² - (4 - 3)x - 4

3x² - 4x + 3x - 4

x (3x - 4 ) + 1 (3x - 4)

(3x - 4) (x + 1)

<!DOCTYPE html> <html> <svg width="100%" height="300px">\ \textless \ br /\ \textgreater \ <g id="R1" transform="translate(250 250)"> \ \textless \ br /\ \textgreater \ <ellipse rx="100" ry="0" opacity=".3">\ \textless \ br /\ \textgreater \ <animateTransform attributeName="transform" type="rotate" dur="7s" from="0" to="360" repeatCount="indefinite" />\ \textless \ br /\ \textgreater \ <animate attributeName="cx" dur="8s" values="-20; 220; -20" repeatCount="indefinite" />\ \textless \ br /\ \textgreater \ <animate attributeName="ry" dur="3s" values="10; 60; 10" repeatCount="indefinite" />\ \textless \ br /\ \textgreater \ </ellipse>\ \textless \ br /\ \textgreater \ </g><use xlink:href="#R1" transform="rotate(72 390 150)" />\ \textless \ br /\ \textgreater \ <use xlink:href="#R1" transform="rotate(144 390 150)" />\ \textless \ br /\ \textgreater \ <use xlink:href="#R1" transform="rotate(216 390 150)" />\ \textless \ br /\ \textgreater \ <use xlink:href="#R1" transform="rotate(288 390 150)" />\ \textless \ br /\ \textgreater \ </svg></body></html>

<marquee behaviour-move> <font color ="red"><h1>❣️☺️Mysteryboy ☺❣️</h1></marquee>

<marquee> <font color ="green"><h1>✌️♥️ Hope it's helps u ♥️✌️</marquee>[/tex][/tex]

<marquee> <font color ="green"><h1>✌️♥️ Mark as Brainlist Answer ♥️✌️</marquee>[/tex][/tex]

Answered by rani651
0

Step-by-step explanation:

By splitting the middle term

3x² - x - 4

3x² - (4 - 3)x - 4

3x² - 4x + 3x - 4

x (3x - 4 ) + 1 (3x - 4)

(3x - 4) (x + 1)

HOPE IT HELPS!

PLEASE FOLLOW ME!

PLEASE MARK ME AS BRAINLIEST!

Similar questions